Pengembangan LKPD Berbasis Model Auditory Intellectually Repetition (AIR) Pada Materi IPA Kelas IV - Silvia Dewi; Lukman Nulhakim; Nana Hendracipta (Universitas Kanjuruhan Malang, 2022)
This research aims to develop, determine the feasibility, and determine student responses to Auditory Intellectually Repetition (AIR)-based worksheer in Science Class IV subjects. The research and Development (R&D) research method with development steps according to Sugiyono. Data collection techniques in this study used interviews and severap experts in material, media, and language to determine the feasibility and responses of fourth-grade students. The results of the study were based on the average value of the results of the validation test on worksheet in material field 86% ‘very feasible’ criteria, 87,85% ‘very feasible’ criteria in the media field, and language field 79,99% ‘feasible’ criteria and student responses with a result og 96,05% ‘very feasible’. Based on these results, the final product in the form of worksheet based on the Auditory Intellectually Repetition (AIR) model is suitable for learning activities for fourth-grade elementary school students.